The prevalence of hearing loss in HIV-infected South African adolescents on antiretroviral therapy - Banga, Agatha Tafadzwa (Centre for Infectious Disease Epidemiology and Research (CIDER), 2018)
Objective: To investigate hearing loss among perinatally HIV-infected (PHIV+) adolescents on antiretroviral therapy (ART), and HIV-non-infected (HIV-) adolescents in Cape Town, South Africa. Methods: A cross-sectional analysis was carried out to describe the prevalence, nature and predictors (demographic, past medical history, clinical findings) of hearing loss in adolescents between 9 and 14 years of age. Screening pure-tone air-conduction (AC) thresholds above 30 decibels (dB) were considered to be indicative of debilitating hearing loss. Statistical analysis included univariate analysis and multivariate logistic regression. Results: The cross-sectional analysis included data from 540 participants; consisting 273 males (51%), 267 females, 432 PHIV+ and 108 HIV-, with a median age of 12 years. Hearing impairment was observed in 19% of all the adolescents in the study. Multivariate analysis showed the following predictors for any hearing loss: an unmarried primary caregiver (odds ratio (OR) 0.59; 95% confidence interval (CI), 0.39;0.91, p = 0.015), being female (OR 1.67; 95% CI, 1.12;2.51; p = 0.013) and reports of being troubled by ear pain or discharge in the last month (OR 2.54; 95% CI, 1.55;4.17; p = <0.001) after adjustment. Univariate analysis showed an association between hearing loss and a longer duration on ART among PHIV+ adolescents (OR 1.80, 95%CI 1.17;2.75, p = 0.007). Conclusion: The prevalence of hearing loss appears to be comparable between PHIV+ and HIVadolescents in Cape Town. In low resource settings, a history of ear pain or discharge within the last month may be used as a screening tool for a hearing assessment, and guide referral for formal hearing tests.